"I Tell Them What I Can Feel and How Far My Legs Can Bend": Optimizing Sexual Satisfaction for Women with Spina Bifida. Issue 9 (11th July 2020) - Streur, Courtney S.; Schafer, Christine L.; Garcia, Valerie P.; Quint, Elisabeth H.; Wiener, John S.; Sandberg, David E.; Kalpakjian, Claire Z.; Wittmann, Daniela A.
Abstract: Background: There is a high reported rate of sexual dysfunction among women with spina bifida, but little is known about the etiology of this or how sexual satisfaction could be improved. Aim: To identify, through the words of women with spina bifida, perceived causes of diminished sexual satisfaction and recommendations to optimize partnered sexual encounters. Methods: In this qualitative study, we conducted semi-structured individual interviews with 22 women with spina bifida (median age 26.5 years, range 16–52 years) who have had a romantic partner. Using Grounded Theory, interviews were independently coded by 3 reviewers. Disagreements were resolved by consensus. Outcomes: We identified overlapping themes of issues women experienced during sexual intimacy and strategies they learned to improve sexual encounters. Results: 7 salient themes emerged from the data: (i) fear of rejection with resulting difficulty setting boundaries and the risk of coercion; (ii) conflict between spontaneity and self-care in sexual encounters; (iii) worry about incontinence during sex; (iv) trial and error in learning optimal sexual positions; (v) decreased genital sensation; (vi) safety considerations; and (vii) sharing advice with other women with spina bifida. Clinical Implications: As sexual satisfaction is influenced by physical features as well as psychological, interpersonal, and sociocultural factors, optimizing sexual satisfaction of women with spina bifida is best managed with a holistic approach utilizing a biopsychosocial model. Strengths & Limitations: The sample included women with a diverse range of functional impairments. Women were forthright with their comments and thematic saturation was reached. Recruitment was primarily from a single Midwestern institution, which may have limited sampled perspectives. Conclusion: While women with spina bifida encounter challenges during sexual encounters, strategies focused on improving communication with partners and addressing specific physical considerations can potentially enhance their sexual experiences.